2008
DOI: 10.1016/j.neuron.2008.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Translation of Arc/Arg3.1 Selectively Mediates mGluR-Dependent LTD through Persistent Increases in AMPAR Endocytosis Rate

Abstract: Salient stimuli that modify behavior induce transcription of Activity regulated cytoskeleton-associated protein (Arc/Arg3.1) and transport Arc mRNA into dendrites, suggesting that local Arc translation mediates synaptic plasticity encoding such stimuli. Here we demonstrate that long-term synaptic depression (LTD) in hippocampal neurons induced by group 1 metabotropic glutamate receptors (mGluRs) relies on rapid translation of Arc. MGluR-LTD induction causes long-term increases in AMPA receptor endocytosis rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
550
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(589 citation statements)
references
References 56 publications
26
550
5
1
Order By: Relevance
“…For example, activity-regulated cytoskeletal associated (Arc) protein is synthesized within dendrites in an activity-and group I mGluR-dependent manner where it associates with components of AMPAR endocytosis machinery and has been shown to actively maintain LTD (Park et al, 2008;Waung et al, 2008). Within striatal regions, Arc protein expression is robustly induced following re-exposure to cocaine-paired stimuli and modulates extinction of drugseeking behavior (Hearing et al, 2011;Hearing et al, 2008).…”
Section: Mechanisms Underlying Synaptic Depotentiationmentioning
confidence: 99%
“…For example, activity-regulated cytoskeletal associated (Arc) protein is synthesized within dendrites in an activity-and group I mGluR-dependent manner where it associates with components of AMPAR endocytosis machinery and has been shown to actively maintain LTD (Park et al, 2008;Waung et al, 2008). Within striatal regions, Arc protein expression is robustly induced following re-exposure to cocaine-paired stimuli and modulates extinction of drugseeking behavior (Hearing et al, 2011;Hearing et al, 2008).…”
Section: Mechanisms Underlying Synaptic Depotentiationmentioning
confidence: 99%
“…As FMRP is confirmed to be a repressor of synaptic protein synthesis (Bear et al, 2004;Bhakar et al, 2012), loss of FMRP in FXS may lead to deficits in synaptic plasticity and information storage. Indeed, it has been reported that FMRP can negatively regulate proteins that trigger AMPA receptor internalization (Park et al, 2008;Waung et al, 2008), and Fmr1 knockout (KO) mice display exaggerated long-term depression in the hippocampus (Huber et al, 2002;Zhang et al, 2009) and cerebellum (Koekkoek et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In neurons, Arc expression is regulated by various stimuli including not only neuronal activity, but also BDNF, cAMP, and PDGF (3)(4)(5)(6). Arc mRNA has been detected in cell bodies, dendrites, and spines after stimulation (7,8), and the Arc protein could be synthesized locally at dendritic spines (9,10). Arc is known to be required for the endocytosis of AMPA receptors (10) and for long-term potentiation (LTP)-induced F-actin stabilization (9,11).…”
mentioning
confidence: 99%
“…Arc mRNA has been detected in cell bodies, dendrites, and spines after stimulation (7,8), and the Arc protein could be synthesized locally at dendritic spines (9,10). Arc is known to be required for the endocytosis of AMPA receptors (10) and for long-term potentiation (LTP)-induced F-actin stabilization (9,11). Okuno et al (12) reported that Arc plays a role in the inverse synaptic tagging of silent synapses; Arc accumulated in silent synapses to reduce surface AMPA receptors (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation